IMPLEMENTASI ASSOCIATION RULE MINING UNTUK MENENTUKAN POLA KOMBINASI MAKANAN DENGAN ALGORITMA APRIORI - Marina Rajagukguk; Rafiqa Dewi; Eka Irawan; Jaya Tata Hardinata; Irfan Sudahri Damanik (Fakultas Ilmu Komputer, Unversitas Muhammadiyah Riau, 2020)
OH5 Hash Cafe is a business that is engaged in the food sector and there is a lot of competition in doing business that is increasingly difficult to do so it is necessary to develop a strategy, this study aims to determine the pattern of food combinations, the method used in this research is the Apriori Algorithm to be able to find out and processed using the Rapid Miner 9.7 software in determining food combination patterns, the Apriori Algorithm is an interesting type of association rule in data mining and an interesting association analysis to produce an efficient algorithm that is high frequency pattern analysis, an association can be identified with two benchmarks, namely: Support and Cofindence. Support is the percentage of item combinations in the database, while Confidence is the strong relationship between items in the association rule.